2014
DOI: 10.1007/s40617-014-0025-0
|View full text |Cite
|
Sign up to set email alerts
|

Positive Peer Reporting in the Classroom: a Review of Intervention Procedures

Abstract: Positive peer reporting (PPR) is a classroom-based intervention to improve social interactions between students using rewards and positive social attention. Along with a variant of the procedure referred to as "Tootling," PPR has demonstrated overwhelmingly positive results since its development. However, a unified, standard protocol for successful implementation of PPR interventions has not yet been established. A review of 24 studies, including 48 separately described cases of PPR in classroom settings, prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 21 publications
(45 reference statements)
0
17
0
Order By: Relevance
“…Similarly, teachers of middle school students in one sample reported that providing praise to students within the context of supporting academic success is one component of teacher behavior that contributes to care and closeness with students (Garza et al, 2014). Murphy and Zlomke (2014) indicated that positive student-teacher interactions support students' social development and can improve their attitude toward school, thereby improving their attitude toward their teacher and classroom learning environment.…”
Section: Evidence Supporting Teacher Praise With Middle and High Schomentioning
confidence: 99%
“…Similarly, teachers of middle school students in one sample reported that providing praise to students within the context of supporting academic success is one component of teacher behavior that contributes to care and closeness with students (Garza et al, 2014). Murphy and Zlomke (2014) indicated that positive student-teacher interactions support students' social development and can improve their attitude toward school, thereby improving their attitude toward their teacher and classroom learning environment.…”
Section: Evidence Supporting Teacher Praise With Middle and High Schomentioning
confidence: 99%
“…Tootling is a relatively novel positive peer reporting procedure first proposed by Skinner et al () and is the opposite of tattling and converse of the term, ‘tooting your own horn.’ Hence, in Tootling, students engage in positive peer monitoring and report their peers' positive, prosocial behaviors, thereby ‘tooting the horn’ of their peers rather than their own. Tootling represents a deviation from typical positive peer reporting interventions, in which students verbally report positive observations of peer behavior (Murphy & Zlmoke, ). In Tootling, students instead monitor and privately record their peers' prosocial behavior on note cards, which are then collected and a randomly chosen sample is read aloud by the teacher.…”
mentioning
confidence: 99%
“…First, negative student commenting is placed on extinction while positive peer reporting via note cards is rewarded. In other words, negative peer interactions are decreased, and positive interactions are increased through differential reinforcement (Murphy & Zlmoke, ). Teacher and peer attention is delivered on a random‐ratio schedule (Schoenfeld, Cumming, & Hearst, ), in which the probability of an individual student receiving attention is proportional to the number of tootles submitted for that student, the total number of tootles generated by the class, and the number of cards read.…”
mentioning
confidence: 99%
“…During PPR sessions, reinforcement is withheld for negative comments and positive comments are praised or rewarded. Therefore, differential reinforcement works to extinguish negative peer comments or statements and increases positive behaviors and statements (Murphy & Zlomke, 2014). The PPR intervention increases opportunities for students to practice exchanging positive social statements with peers.…”
Section: Positive Peer Reportingmentioning
confidence: 99%
“…More specifically, PPR is implemented to give the "recipient" student an incentive to interact appropriately for positive attention while encouraging other "reporter" students to be aware of the recipient's prosocial behaviors rather than focusing on negative actions (Ervin et al, 1996). Consequently, operant reinforcement for prosocial comments works by conditioning recipients to engage in positive interactions with peers more frequently (Murphy & Zlomke, 2014). This may also be helpful for students in the classroom who are reinforced by attention from peers.…”
Section: Positive Peer Reportingmentioning
confidence: 99%